Multi-targeted potential of Pittosporum senacia Putt.: HPLC-ESI-MSn analysis, in silico docking, DNA protection, antimicrobial, enzyme inhibition, anti-cancer and apoptotic activity - Mahomoodally M. F.; Picot-Allain C.; Hosenally M.; Ugurlu A.; Mollica A.; Stefanucci A.; Llorent-Martinez E. J.; Baloglu M. C.; Zengin G. (Elsevier BV, 2019)
Pittosporum senacia (PS) Putt. (Pittosporaceae), indigenous to the Mascarene Islands, is a common ingredient in traditional medicines. However, there is currently a dearth of studies to validate some of these traditional claims. Given the broad traditional uses of PS against several diseases, we aimed to provide a comprehensive insight into the biological and chemical profile of P. senacia. The antioxidant, enzyme inhibitory activity, anticancer, and phytochemical composition of the methanolic extract of P. senacia leaf extracts were studied. The possible interaction and binding mode of the most abundant phytochemicals were studied via in silico docking experiments on tyrosinase and α-glucosidase. The mechanism behind the cytotoxic property of P. senacia extract for MDA-MB-231 was also examined using different methods including 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cell viability test checking apoptosis-associated genes, and wound healing assays. Twenty-six compounds were identified, of which caffeoylquinic acid derivatives, ferulic acid derivative, cinnamoylquinic acid derivative and two other polyphenols (oleuropeine and isoramnetin glucoside) being abundant, have been tested using in silico studies, against α-glucosidase and tyrosinase. The extract (IC50 = 118.8 μg/ml) exhibited time and dose dependent anti-proliferative effect on human breast cancer cell line, MDA-MB-231. According to the expression profile of apoptosis inhibitors and apoptosis promoters genes, expression of Bax and Bak genes were significantly increased compared to Bcl-2 and Birc5 genes. Based on wound healing analysis, cell migration was inhibited after the application of the plant extract. The present findings suggested that PS might be a good candidate as sources of bioactive compounds for designing functional applications.
Keywords: Spectrometry, Mass, Electrospray Ionization; Pittosporaceae; Cell Survival; Apoptosis; Microbial Sensitivity Tests; Gram-Positive Bacteria; Gram-Negative Bacteria; Tumor Cells, Cultured; Humans; Enzyme Inhibitors; Rosales; Antimicrobial; Apoptosis; Diabetes; Mauritius; Pittosporaceae; Anti-Bacterial Agents; Antineoplastic Agents, Phytogenic; Apoptosis; Cell Proliferation; Cell Survival; Chromatography, High Pressure Liquid; DNA; Drug Screening Assays, Antitumor; Enzyme Inhibitors; Gram-Negative Bacteria; Gram-Positive Bacteria; Humans; Microbial Sensitivity Tests; Monophenol Monooxygenase; Plant Extracts; Plasmids; Rosales; Spectrometry, Mass, Electrospray Ionization; Tumor Cells, Cultured; alpha-Glucosidases; Molecular Docking Simulation; Chromatography, High Pressure Liquid; Cell Proliferation; Monophenol Monooxygenase; Plant Extracts; Diabetes; DNA; Antineoplastic Agents, Phytogenic; Anti-Bacterial Agents; Molecular Docking Simulation; Mauritius; Antimicrobial; Drug Screening Assays, Antitumor; Plasmids; 3. Good health